A Case of Aspergillus fumigatus Infection in Emu Chicks - Karunakaran , Sunitha; Nair , G. Krishnan; Nair , N. Divakaran; Mini M. , (Advanced Research in Biological Science Vol. 6, 2023)
The chapter documents a case of Aspergillus fumigatus infection in Emu chicks in an Emu farm of northern Kerala. Aspergillosis is a disease caused by a fungus belonging to Aspergillus species. Seven Emu chicks in the age groups of one week to seven weeks submitted to the Clinical Laboratory, District Veterinary Centre, Palakkad District, from an Emu farm in Northern Kerala (Palakkad district) during 2010 formed the materials for investigation. Detailed post mortem was conducted and gross lesions were recorded. Heart blood and pieces of liver tissue were cultured in Sabouraud’s Dextrose Agar (SDA) aerobically at room temperature. Lungs along with nodule and liver were processed for lacto phenol cotton blue staining and with ten per cent potassium hydroxide solution for direct examination. On examination, numerous small greyish white nodules were seen in the lungs, air sacs, kidney and serosal surface of proventriculus. Dark red liver with necrotic areas and dark coloured spleen were the other lesions. Microscopically the lungs revealed granulomas with central areas of caseation surrounded by mononuclear cells and fibroblasts. PAS positive fungal hyphae could be seen in the lesion. In conclusion, the study stated that control measures should be directed at the prevention, as there is no effective treatment for this disease. The identified infection in the Emu farm could be controlled by fumigation of hatchers using potassium permanganate and formaldehyde and sanitization of eggs before setting them in the incubator, using egg sanitisers.